The role of the Internet in teachers' professional practice: activities and factors associated with teacher use of ICT inside and outside the classroom. Issue 4 (8th August 2017) - Ibieta, Andrea; Hinostroza, J. Enrique; Labbé, Christian; Claro, Magdalena
Abstract: Evidence shows that teachers' use of information and communication technology (ICT) in the classroom is still limited in variety and frequency. However, their use of ICT outside the classroom, while more frequent, has been less studied. Our research aims to identify personal factors associated with teachers' ICT use inside and outside the classroom. Data from a questionnaire administered to a nationwide sample of 6932 teachers in Chile was used to characterise their activities and perceptions associated with ICT. Multiple regression analyses were applied to determine relationships between them. The findings show first, that teachers use ICT more frequently outside the classroom for class preparation; second, that their perceptions of ICT impact on professional practice is the main factor associated with their use of ICT inside and outside the classroom; third, that less experienced teachers use communication tools with colleagues and students more often; and finally, that there is a need to examine teachers' use of (ready-made) Internet resources.